SUBSTANSI AL-MAQÂSHID AL-SYARÎ‘AH DALAM SYARI’AT ISLAM - Muhammad Hasbulloh Huda (LP3M IAI Al-Qolam Malang, 2017)
The conception of maqhasid al shari'ah is the concept of Islamic law in maintaining the existence of human life, which is manifested in the form of the existence of the benefit of mankind. Most of fiqih experts value the principle of benefit as one of the shari'a propositions that can be used as a basis for law enforcement, fatwa or court decision. In the books of fiqih easily can be found laws that are only based on legal matters of kemaslahatan or remove damage. The Sahabahs as the generation who best understands the Shari'a are the most widely used the principle of benefit as a back, many of their actions are in accordance with the principle of this benefit. Keywords: Syariat, Islam, Maslahat